2022
DOI: 10.3390/bios12050354
|View full text |Cite
|
Sign up to set email alerts
|

Acetone Gas Sensor Based on SWCNT/Polypyrrole/Phenyllactic Acid Nanocomposite with High Sensitivity and Humidity Stability

Abstract: We synthesized core-shell-shaped nanocomposites composed of a single-walled carbon nanotube (SWCNT) and heptadecafluorooctanesulfonic acid-doped polypyrrole (C8F-doped-PPy)/phenyllatic acid (PLA), i.e., C8F-doped-PPy/PLA@SWCNT, for detecting acetone gas with high sensitivity and humidity stability. The obtained nanocomposites have the structural features of a sensing material as a C8F-doped-PPy layer surrounding a single-stranded SWCNT, and a PLA layer on the outer surface of the PPy as a specific sensing laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This resulted in the formation of a rod-shaped nanostructure with SWCNT at the core surrounded by PPy–PLA ( Scheme 1 ). A previous study reported that PLA is chemically bonded with the PPy chain and reacts selectively with a specific gas such as acetone [ 26 ]. The resulting products can maintain long-term dispersion stability in aqueous solution without precipitation due to its excellent dispersion characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This resulted in the formation of a rod-shaped nanostructure with SWCNT at the core surrounded by PPy–PLA ( Scheme 1 ). A previous study reported that PLA is chemically bonded with the PPy chain and reacts selectively with a specific gas such as acetone [ 26 ]. The resulting products can maintain long-term dispersion stability in aqueous solution without precipitation due to its excellent dispersion characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The rod-shaped SWCNT/C4F-PPy nanocomposite was synthesized using an emulsion polymerization technique described in a previous paper [ 26 ]. The synthesis proceeded in five steps.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The polymer as well as polymer nanocomposite sensors prepared showed excellent linearity with gas concentration because of the increased electron hopping by the addition of Fe 2 O 3 and Co‐Fe 2 O 3 nanoparticles. Better sensing response shown by the copolymer nanocomposites compared to the pure polypyrrole can be attributed to the increased number of positive charges (polarons or bipolarons) on the polymer backbone 33 …”
Section: Resultsmentioning
confidence: 99%